Serum Albumin Redox States: More Than Oxidative Stress Biomarker - Fuka Tabata; Yasuaki Wada; Satomi Kawakami; Kazuhiro Miyaji (MDPI AG, 2021)
Serum albumin is the most abundant circulating protein in mammals including humans. It has three isoforms according to the redox state of the free cysteine residue at position 34, named as mercaptalbumin (reduced albumin), non-mercaptalbumin-1 and -2 (oxidized albumin), respectively. The serum albumin redox state has long been viewed as a biomarker of systemic oxidative stress, as the redox state shifts to a more oxidized state in response to the severity of the pathological condition in various diseases such as liver diseases and renal failures. However, recent ex vivo studies revealed oxidized albumin per se could aggravate the pathological conditions. Furthermore, the possibility of the serum albumin redox state as a sensitive protein nutrition biomarker has also been demonstrated in a series of animal studies. A paradigm shift is thus ongoing in the research field of the serum albumin. This article provides an updated overview of analytical techniques for serum albumin redox state and its association with human health, focusing on recent findings.